Local Release of TGF‐β Inhibitor Modulates Tumor‐Associated Neutrophils and Enhances Pancreatic Cancer Response to Combined Irreversible Electroporation and Immunotherapy. Issue 10 (7th February 2022) - Peng, Huiming; Shen, Jian; Long, Xin; Zhou, Xiaoqi; Zhang, Jiaqi; Xu, Xina; Huang, Teng; Xu, Hui; Sun, Shuguo; Li, Chun; Lei, Ping; Wu, Heshui; et al.
Abstract: Pancreatic cancer is a deadly disease with little response to standard therapies. Irreversible electroporation (IRE) has emerged as a novel ablative technique for the clinical treatment of pancreatic cancer. Combinations of IRE and immunotherapies, including anti‐programmed death 1 ( α PD1) immune checkpoint blockade, have shown promising efficacy in both preclinical and clinical studies. However, tumor recurrence remains an obstacle that needs to be overcome. It herein is shown that IRE induces a substantial infiltration of neutrophils into pancreatic tumors. These neutrophils are then polarized into a protumor phenotype by immunosuppressive cues, in particular transforming growth factor β (TGF‐ β ). Using glutathione‐responsive degradable mesoporous silica nanoparticles loaded with SB525334, an inhibitor of TGF‐ β 1 receptor, it is demonstrated that local inhibition of TGF‐ β within the tumor microenvironment promotes neutrophil polarization into an antitumor phenotype, enhances pancreatic cancer response to combined IRE and α PD1 therapy, and induces long‐term antitumor memory. The therapeutic efficacy is also attributed to tumor infiltration by CD8 + cytotoxic T cells, depletion of regulatory T cells, and maturation of antigen‐presenting dendritic cells. Thus, modulating neutrophil polarization with nanomedicine is a promising strategy for treating pancreatic cancer. Abstract : Treatment of pancreatic tumor by irreversible electroporation (IRE) induces a rapid infiltration by neutrophils, which polarize into a protumor phenotype and negatively correlate with therapeutic outcome. Local release of transforming growth factor‐ β inhibitor within the tumor microenvironment promotes neutrophils polarization toward an antitumor phenotype and enhances tumor response to combined IRE and immunotherapy.